Sponsored Search Auction and the Revenue- Maximizing Number of Ads per Page - Pallavi Pal (Center for Economic Studies and ifo Institute (CESifo), 2023)
In this paper, I derive a new method to identify the distribution of the advertiser's ad-value in the sponsored search auction, explicitly looking at weighted Generalized Second Price auction (GSPw henceforth). Compared to previous literature, this method incorporates a weaker and more realistic assumption of 'incomplete information' on advertisers' private information. Additionally, I evaluate how much the advertisers shade their bid below their value, defined as bid shading amount. The results show that the bid shading is very small; the 50th percentile of the bid shading upper bound is below by 0.2% of their value. The low amount of bid shading is due to high competition intensity in the online ad market as the number of competing bids in the online ad market is very large. The bid shading calculation can also shed light on how the change of ad auction will impact the ad revenue.
Keywords: 330